Cairasco, humanista - Santana Henríquez, Germán; Rodríguez Díaz, Luis Miguel (2010)
La obra de Bartolomé Cairasco de Figueroa fusiona la herencia humanista y la cultura cristiana en una nueva forma de escribir que plantea la realidad insular como escenario de la gran epopeya del martirologio cristiano. Se trata de adoptar y trasladar una tradición para ponerla al servicio de la enunciación de su realidad. La palabra se convierte así en el lugar de encuentro donde el mito se actualiza y se pone al servicio de un nuevo imaginario.
Bartolomé Cairasco de Figueroa’s work merges the humanistic legacy with the Christian culture in a new way of writing where the insular environment is taken as the scene of the Christian martyrology great epic poem. A tradition is adapted and moved in order to put it at the disposal of reality enunciation. The word is transformed thus in the meeting point where the myth is updated and put at the disposal of a new imaginary.
Keywords: Cairasco de Figueroa, Bartolomé; Humanistas